La gente cambia la tierra - Bauer, David, 1963-; Bauer, David, 1963- (Mankato, Minn. : Yellow Umbrella Books, 2005)
Describe como la gente cambia el paisaje cuando cultivan la tierra o construyen pueblos y ciudades.
Presents a children's book that describes the many ways that people have changed the landscape such as when farmers cultivate the land, when cities and towns are built, as well as bridges, tunnels, and dams.
Includes index.
Translation of: People change the land.
Text in Spanish.
Keywords: Civil engineering; Land use